Vichy mineralizing water with hyaluronic acid is effective and well tolerated as an adjunct to the management of various dermatoses and after esthetic procedures. (3rd December 2019) - Tan, Jerry; Spada, Julieta; Orlandi, Cecilia; Kerscher, Martina; Anfilova, Maryna; Abdulla, Sonya; Floriánová, Adriana; Preisz, Klaudia; Altmayer, Anita; Delva, Catherine; Kerob, Delphine; Goldobina, Maiia; et al.
Abstract: Introduction: M89, containing 89% of Vichy mineralizing water and hyaluronic acid, has been developed to reinforce the skin barrier and to improve skin quality. Aim: To assess efficacy and tolerability of M89. Method: Observational survey of subjects with facial dermatoses or after esthetic procedures. M89 served as adjunct to conventional therapy. Clinician assessments of erythema, desquamation, irritation and patient‐reported dryness, burning, itching, and stinging/tingling were conducted at baseline and 4 weeks. At 1 week and 4 weeks, patient assessed tolerance and satisfaction with M89. Results: A total of 1630 subjects participated; 92.5% were females. Mean age was 41.1 ± 11.3 years. Dermatological indications accounted for 32.5%, procedures for 67.5%. At 4 weeks, in subjects with dermatoses, erythema had resolved or improved in 68.0%, desquamation in 83.4%, and irritation in 93.3%. Dryness, burning, itching, and stinging/tingling scores had decreased by 63.8%, 81.8%, 70.9%, and 85.2%, respectively (all P ≤ .0001); 75.7% considered that their skin was sufficiently hydrated. In the procedure group, erythema had resolved or improved in 72.5%, desquamation in 75.2%, and irritation in 88.1%. Dryness, burning, itching, and stinging/tingling scores had decreased by 62.1%, 78.8%, 70.0%, and 84.2%, respectively (all P ≤ .0001); 74.1% considered that their skin was sufficiently hydrated. Almost all subjects reported soothed skin and satisfaction with product texture. Subject and investigator satisfaction was very high. Conclusion: M89 significantly improves skin signs and symptoms after 4 weeks of continued use with no tolerance issues in subjects with dermatological indications. Moreover, subjects who have had recently undergone esthetic procedures M89 allowed a satisfying skin recovery.